Representações sociais sobre a morte do paciente para graduandos de enfermagem: o ensino-aprendizagem do cuidado no fim da vida - Ouchi, Janaína Daniel (2014)
The care process, which involves the practice of nursing care to patients who are in the terminal phase of life, in addition to professional competence requires emotionally prepared to accept the moment of death. This force that nurse needs to have, is not always possible due to their (dis) academic preparation. Therefore it is necessary to include the issue of termination of life in nursing education, offering tools for development of total nursing care. Understand the social representations of nursing students about death and loss of the patient, revealing the weaknesses of this approach in the teaching learning process can contribute to a curriculum proposal that contemplates the development of trained nurses for care at end of life. Objectives: Understand the representations of nursing students about death; identify the feelings of the graduating before death the patient to their care; describe how undergraduates evaluate their training for care at end of life. Methods: This is a qualitative and quantitative study, based on the Theory of Social Representations, conducted through oral interviews with 23 graduating students of undergraduate nursing. The interview covered three guiding questions concerning representations of death, feelings caused by the death of the patient and evaluation of training for care at end of life. The statements were organized according to the Collective Subject Discourse and analyzed on thematic analysis method. Results: It was found that the profile of the participants was mostly represented by young adults, women who do not work in the nursing field. Discourses about the representations of death fell mainly about death as a passage. These participants believe that life, though invisible, continues after death. There are also respondents who regard death as a process inherent to life and get hold of it. Others see death as shocking, devastating. Multiple feelings surfaced this experience: frustration, shock, empathy, sadness, relief, loneliness, guilt. All study participants showed dissatisfaction with the teaching and learning of care at the end of life process. They considered themselves unprepared to care at end of life, mentioned that the death is not addressed in theory and practice, cited many missing content in their training, the teacher would like to have on the practice field and problematize the practice in the classroom. Conclusion: In addition to the technical and scientific knowledge about care at the end of life, addressing the feelings and different situations in which death is presented and individual coping difficulties that cannot be forgotten in the curricula of graduate courses in Nursing. Strategies of teaching-learning and problem-solving skills of nursing faculty for these approaches are equally important